Cross-owners and bond issue pricing: coordination or collusion? - Shangkun Liang; Sichao Wang; Kaijuan Gao (China Journal of Accounting Research)
Using a sample of listed Chinese firms from 2007 to 2020, we investigate the governance implications of cross-ownership in corporate bond markets. We find that cross-ownership significantly reduces bond issuance spreads, suggesting that synergistic governance effects outweigh potential collusion risks. This effect operates through two channels: reducing information asymmetry between shareholders and creditors and lowering firm risk. The effect is stronger when cross-owners hold shares in more peer firms and retain shares longer but weaker for state-owned enterprises, long-term bonds and firms with robust information intermediaries. Our findings contribute to the corporate governance literature by demonstrating how cross-ownership enhances creditor protection, providing insights into optimizing ownership structures for debt financing, particularly in emerging markets with inadequate institutional monitoring.